2004
DOI: 10.1620/tjem.202.31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alcohol Consumption on Hepatocellular Injury in Japanese Men

Abstract: To clarify the effects of alcohol consumption on hepatocellular injury, we examined aspartate and alanine aminotransferases (AST and ALT), and -glutamyltransferase (GGT), together with weekly alcohol consumption calculated from a self-rating questionnaire, in 1113 Japanese salesmen. The thresholds of associations between alcohol consumption and liver markers were estimated by the benchmark dose (BMD) method. The AST, ALT and GGT were positively correlated with alcohol intake (p<0.001), as well as age and body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 25 publications
3
16
0
1
Order By: Relevance
“…Recently Dakeishi et al reported that hepatocellular injury, as indicated by elevation of AST could emerge only when the alcohol intake is >50 gm/day. [19] This concurs well with our findings where the mean alcohol consumption was 300 g/day and AST levels were also elevated significantly. The AST appears to be the primary marker of hepatocellular injury because it is more specific than other liver enzymes for detecting alcohol induced diseases.…”
Section: Discussionsupporting
confidence: 93%
“…Recently Dakeishi et al reported that hepatocellular injury, as indicated by elevation of AST could emerge only when the alcohol intake is >50 gm/day. [19] This concurs well with our findings where the mean alcohol consumption was 300 g/day and AST levels were also elevated significantly. The AST appears to be the primary marker of hepatocellular injury because it is more specific than other liver enzymes for detecting alcohol induced diseases.…”
Section: Discussionsupporting
confidence: 93%
“…A total of 100% ethanol equivalent dose (g/wk) was calculated for each subject, using a questionnaire reported previously 11) . In the solvent workers, concentrations of toluene, xylene, styrene, and n-hexane were measured using passive gas samplers (Sibata Co., Japan) worn through the day, and were estimated as 8-h time-weighted average concentration (ppm) by gas chromatograph mass spectrometry (Qmass910 Mass Spectrometer; Perkin Elmer Inc., USA) with Spelcowax 10 column separation and single ion monitoring detection.…”
Section: Methodsmentioning
confidence: 99%
“…For ethanol, BMD modelling results from long‐term animal experiments as well as from large human epidemiological studies are available in the literature (Table ) . We additionally provide BMD modelling of a study on breast cancer .…”
Section: Resultsmentioning
confidence: 99%